Effect Of Additional Lumbal Traction In Tens And Short Wave Diathermi Interventions On Lower Pain In Nucleuspulposus Hernia Patients at RSUP.H.Adam Malik Medan Hospital in 2021 - Sabirin Berampu; Raynal Ignasius Ginting; Denniaty Sembiring (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Objective: To determine the effect of the addition of lumbar traction in the intervention of Tens and Short Wave Diathermy on the Intensity of Low Back Pain in Lumbar Hernia Nucleus Pulpos Patients 4 – 5 Methods: This study used a quantitative research type with a quasi-experimental approach to pre-test and post-test design with two groups. The samples of this study were 12 people in the TL, TENA, SWD group and 12 people in the TENS & SWD group. Results: normality test with Shapiro Wilk Test obtained data before and after treatment groups I and II data were normally distributed. The results of hypothesis testing with One Sample Test before and after treatment I are p value 0.001 where p <0.05 this means Ho is rejected so that the results of the One Sample Test treatment II are p value 0.001 where p <0.05 this means Ho is rejected so that it can be concluded that TL, TENS & SWD and TENS & SWD exercises can both reduce the pain of Hernia Nucleus Pulposus Lumbar 4-5 . While the results for the Independent Sample T-Test test, namely the difference between treatment group I and treatment group II, p 0.09. Conclusion: There is no significant difference between TL, TENS & SWD and TENS & SWD in reducing pain of Hernia Nucleus Pulposus Lumbar 4-5.